STRATEGI PEMASARAN TERUMBU KARANG BUDIDAYA PADA CV BALI AQUARIUM, BADUNG, PROPINSI BALI - IGA OKA SURYAWARDANI; PUTU KIRANA PATNI; I NYOMAN GEDE USTRIYANA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
ABSTRACT The objectives of this research are to understand the marketing strategy undertaken by CV. Bali Aquarium, and to develop alternative marketing strategy that can be implemented by CV. Bali Aquarium. CV. Bali Aquarium undertakes an export business of coral. The coral production is undertaken by coral propagation technology that is located far away from the original coral habitat. The results indicate that CV. Bali Aquarium has developed marketing strategy of segmentation, targeting, positioning, differentiation, marketing mix (product, price, and place), selling, service and process. However, brand image and promotion have not been developed yet. Alternative marketing strategy that needs to be developed and implemented by CV. Bali Aquarium is brand image and promotion. This proposed marketing strategy should take advantage of the coral propagation technology used by the company in its coral transplantation production. This technology is considered to be safe to the environment and sustainable; therefore it will strengthen its position to the customer’s mind. Keywords: Positioning, Differentiation, Brand Image, Propagation Technology. ABSTRAK Penelitian ini bertujuan untuk mengetahui strategi pemasaran yang dikembangkan oleh CV. Bali Aquarium, dan untuk mengembangkan alternatif strategi yang bisa diterapkan oleh CV. Bali Aquarium. CV. Bali Aquarium merupakan perusahaan yang mengekspor terumbu karang. Produksi terumb karang dilakukan dengan menggunakan teknik propagasi di lokasi penangkaran yang juah dari habitat asli terumbu karang. Hasil penelitian menunjukkan bahwa CV. Bali Aquarium telah mengembangkan strategi segmentation, targeting, positioning, differentiation, marketing mix (product, price, place), selling, service and process. Namun, brand image dan promosi belum dikembangkan oleh CV. Bali Aquarium. Alternatif strategi yang bisa dikembangkan oleh CV. Bali Aquarium adalah memperkokoh brand image perusahaan dengan memanfaatkan keunggulan teknik propagasi dalam menjaga kelestarian terumbu karang dan keberlanjutan lingkungan. Keunggulan teknik propagasi ini juga dapat dimanfaatkan dalam kegatan promosi sehingga positioning CV. Bali Aquarium semakin kuat di benak kosumen. Keywords: Posisi, Differensiasi, Brand Image, Teknologi Perbanyakan.